P083 Comorbid TNF-mediated heart valve disease and chronic polyarthritis share common mesenchymal aetiopathogenesis. (21st February 2018) - Ntari, L; Sakkou, M; Chouvardas, P; Mourouzis, I; Prados, A; Denis, MC; Karagianni, N; Pantos, C; Kollias, G
Abstract : Objectives: Rheumatoid arthritis (RA) is a chronic condition characterised by prolonged inflammation of the joints leading to bone and cartilage destruction. The key molecular and cellular regulators of RA pathology are the Tumour Necrosis Factor (TNF) and the mesenchymal-origin Synovial Fibroblasts (SFs), respectively. Apart from the joint pathology, RA patients also show higher morbidity rates, mainly due to the development of extraarticular conditions including cardiovascular, gut and skin disease manifestations. The Tg197 arthritis model develops TNF-driven and mesenchymal synovial fibroblasts (SFs)-dependent polyarthritis. Here, we investigate whether this model develops, similarly to human patients, co-morbid heart pathology and we explore cellular and molecular mechanisms linking arthritis to cardiovascular comorbidities. Methods: The established human TNF-transgenic model of arthritis (Tg197) was used to evaluate possible arthritis-related cardiovascular disease. We further studied the role of Valve Interstitial Cells (VICs) in the pathology, using the ColVI-Cre mouse which specifically targets mesenchymal cells. Tg197 ColVI-Cre Tnfr1 fl/fl and Tg197 ColVI-Cre Tnfr1 cneo/cneo mice were used to explore the role of mesenchymal TNF signalling in the developing heart valve disease. Similarities of pathogenic VICs and SFs were analysed by RNA-sequencing. Results: Tg197 mice develop left-sided heart valve disease, characterised by valvular fibrosis with minimal signs of inflammatory cell infiltration and thickened areas, consisting almost entirely of ColVI -expressing mesenchymal VICs, indicating proliferation of this cell type as a hallmark of the observed phenotype. Development of the pathology results in valve stenosis and left ventricular dysfunction, accompanied by arrhythmic episodes and, occasionally, valvular regurgitation. TNF-dependency of the pathology was indicated by the disease amelioration following pharmacological inhibition or genetic ablation of TNF-signalling. Interestingly, Tg197-derived VICs exhibited an activated phenotype ex vivo, resembling the activation of pathogenic Tg197-derived SFs. A significant functional correlation between these two mesenchymal cells was further supported by RNA-seq analysis, suggesting common pathogenic cellular mechanisms operating in arthritis and cardiovascular comorbidities. Conclusions: TNF-mediated joint pathologies, commonly associated with comorbid heart valve disease, are efficiently modelled in Tg197 arthritis model and are commonly underlined by mesenchymal cell-specific pathogenic mechanisms. Disclosure of interest: None declared